(untitled) (Zaporizhzhia Historical Review, 2021)
The author examines the events in the southern region of Ukraine within the period of Directory of the Ukrainian popular republic on the basis of numerous sources. The article emphasizes that the results of the policy of Directory in the south of Ukraine were of limited character. Directory of the Ukrainian popular republic failed to spread its power even on the southern territory of Ukraine, which was controlled by the Ukrainian state headed by P. Skoropadskyi. The main reason of limitation of power of Directory in the southern region of Ukraine was an external factor mainly presented by the Russian White Guards and Bolsheviks.